"Beset", "besete" of "beserk"?: besinning oor enkele begrippe binne die kerklike diens van bevryding van bose magte - J. P. J. Theron (Acta Theologica)
Concepts used in literature with regard to the church’s ministry of deliverance from evil spirits are discussed. The inadequacies of the terms “demon-possessed” and “possession” and its Afrikaans equivalents in this context, insofar as they sometimes denote “ownership” or “heavy manifestation”, are pointed out. The ways in which Bible translators have dealt with these problems are scrutinised. Alternative terms are offered as part of the development of a relevant practical theological theory.